Por detrás das telas: uma análise da postura reativa das vítimas de cyberbullying - Vaz, Thaís Emília Rodrigues (Universidade Federal de São Carlos, 2017)
Cyberbullying is characterized by virtual violence that spreads through the technological media connected to the Internet, in which there is the distribution of repetitive episodes of exposure, humiliation, aggression and threats directed at the particularities of the victims. Thus, the propagators of Cyberbullying, using the speed with which the posts are shared by Cyberspace, aim to reach the public by disseminating content in which victims are caricatured and their faces become the image of their expositions and humiliations. Thus, many victims of Cyberbullying, using the same viral context of virtual social networks, are instigated to reveal details and repercussions of their cases, evidencing the forms of aggression, characteristics of the aggressors and viewers. These victims still give instructions on how a user can act and protect themselves from virtual violence. Based on the need to investigate the reactive nature of Cyberbullying victims and to observe if this behavior causes significant impacts in online communities, this study intends to analyze video material and campaigns against Cyberbullying attacks, qualifying the reaction of users against these depositions.
Keywords: Redes sociais virtuais; Violência virtual; Virtual violence; Virtual social networks; Cyberbullying; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO